DYNAMICS OF RECRUITMENT AND STRATEGIC LEADERSHIP IN IMPROVING BAWASLU'S PERFORMANCE - Iin Irwanto; Marlina Widiyanti; Sulastri Sulastri; Zunaidah Zunaidah (Green Publisher, 2023)
Popular sovereignty is one of the characteristics of a democratic country. Indonesia as a democratic country realizes people's sovereignty by holding direct, general, free, secret, honest and fair elections. Thus, it is necessary for Bawaslu to play a role in avoiding potential violations at every stage of the election. However, this is not easy, challenges that arise that can hinder Bawaslu's performance are recruitment and strategic leadership. This research aims to determine the various dynamics of recruitment and strategic leadership in improving Bawaslu's performance. The method used in this research is the library study method by reviewing and/or exploring various journals, books and documents related to research. The research results showed that the dynamics of recruitment and strategic leadership of Bawaslu had an impact on the effectiveness of election monitoring. Recruitment based on relevant skills and qualifications is key. Bawaslu leaders also need to have a clear vision and mission in order to improve their performance. With strong recruitment and leadership, Bawaslu can fulfill its responsibilities in ensuring fair, honest and democratic elections